Hubungan Jumlah Rakaat Salat Dhuha terhadap Peningkatan Detak Jantung - Prasetya, Moch.Arief; Hasan, Muhammad; Sofiana, Kristianningrum Dian (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Salat is a muslim worship performed with the movement and reading. Salat types of physical activity with light intensity that can affect heart rate. Heart rate increases in physical activity according to the increase in intensity. This study aims to determine correlation of the number rakaat salat dhuha for increased heart rate. This type of research is analytic observational with a quasi experimental design. The total sample of 42 is divided into 6 treatments, each treatment contains 7 respondents. The sampling technique used a simple random sampling method. The research was conducted from November 2020 to April 2021 using respondents' observations. Data analysis used One Way Anova test and Pearson test. The results of the One Way Anova test, which is a significance value of 0.001 indicating that there is a difference in the increase in heart rate prayer intensity and the results of the Pearson test analysis, namely the value of r or the correlation coefficient of 0.637 and a significant value of=0.00 shows a strong relationship between prayer intensity and an increase in heart rate. The conclusion of this study is that the addition of rakaat salat dhuha increases the heart rateKeyword: Heart Rate, Salat Dhuha